Author 
Message 
TAGS:

Hide Tags

Current Student
Status: Persevere
Joined: 09 Jan 2016
Posts: 123
Location: Hong Kong
GPA: 3.52

For all x, the expression x* is defined to be ax + a, where a is...... [#permalink]
Show Tags
22 May 2016, 23:00
2
This post was BOOKMARKED
Question Stats:
91% (00:48) correct 9% (00:36) wrong based on 291 sessions
HideShow timer Statistics
For all \(x\), the expression \(x^*\) is defined to be \(ax + a\), where \(a\) is a constant. What is the value of \(2^*\)? (1) \(3^* = 2\) (2) \(5^* = 3\)
Official Answer and Stats are available only to registered users. Register/ Login.



SVP
Joined: 06 Nov 2014
Posts: 1889

Re: For all x, the expression x* is defined to be ax + a, where a is...... [#permalink]
Show Tags
23 May 2016, 00:02
nalinnair wrote: For all \(x\), the expression \(x^*\) is defined to be \(ax + a\), where \(a\) is a constant. What is the value of \(2^*\)?
(1) \(3^* = 2\) (2) \(5^* = 3\) x* = ax + a = a (x + 1) 2* = ? Statement 1: 3* = 2 or 3a + a = 2 a = 1/2 Hence 2* = (1/2)*(2 + 1) = 3/2 SUFFICIENT Statement 2: 5* = 3 Or 5a + a = 3 a = 1/2 Hence 2* = (1/2)*(2 + 1) = 3/2 SUFFICIENT Correct Option: D



Manager
Joined: 03 May 2015
Posts: 246
Location: South Africa
Concentration: International Business, Organizational Behavior
GPA: 3.49
WE: Web Development (Insurance)

Re: For all x, the expression x* is defined to be ax + a, where a is...... [#permalink]
Show Tags
24 May 2016, 04:54
Trying to solve these equations is unnecessary and in 90% of DS questions a waste of time A) 3a + a = 2 Linear eqn with 1 variable, 1 solution. sufficient 2) 5 a + a = 6 Same reasoning as above Answer : D
_________________
Kudos if I helped



Intern
Joined: 27 Apr 2015
Posts: 40

For all x, the expression x* is defined to be ax + a, where a is...... [#permalink]
Show Tags
Updated on: 19 Dec 2017, 11:31
nalinnair wrote: For all \(x\), the expression \(x^*\) is defined to be \(ax + a\), where \(a\) is a constant. What is the value of \(2^*\)?
(1) \(3^* = 2\) (2) \(5^* = 3\) Given =>x*=ax+a =>x*=a(x+1) Therefore =>2*=a(2+1) =>2*=3a  (1)so if we can find the value of 'a' we can hav the value of 2* Now Statement 1 says 3*=2 3*=4a from (1)=> 4a=2 => a=2/4=1/2 sufficient Statement 2 says 5*=3 5*=6a from (1)=> 6a=3 => a=3/6=1/2 sufficient Therefore option 'D' Thanks
Originally posted by dineshril on 19 Dec 2017, 07:47.
Last edited by dineshril on 19 Dec 2017, 11:31, edited 1 time in total.



DS Forum Moderator
Joined: 22 Aug 2013
Posts: 1031
Location: India

Re: For all x, the expression x* is defined to be ax + a, where a is...... [#permalink]
Show Tags
19 Dec 2017, 08:50
1
This post received KUDOS
dineshril wrote: nalinnair wrote: For all \(x\), the expression \(x^*\) is defined to be \(ax + a\), where \(a\) is a constant. What is the value of \(2^*\)?
(1) \(3^* = 2\) (2) \(5^* = 3\) Given =>x*=ax+a =>x*=a(x+1) Therefore =>2*=a(2+1) =>2*=3a  (1)so if we can find the value of 'a' we can hav the value of 2* Now Statement 1 says 3*=2 3*=4a from (1)=> 4a=2 => a=2/4=1/2 sufficient Statement 2 says 5*=3 5*=6a from (1)=> 6a=3 => a=3/6=1/2 sufficient Therefore option 'E' Thanks Hi Correct solution. But when each statement alone is sufficient to answer a question, the answer is D I guess that was a typo



Intern
Joined: 27 Apr 2015
Posts: 40

Re: For all x, the expression x* is defined to be ax + a, where a is...... [#permalink]
Show Tags
19 Dec 2017, 11:30
amanvermagmat wrote: dineshril wrote: nalinnair wrote: For all \(x\), the expression \(x^*\) is defined to be \(ax + a\), where \(a\) is a constant. What is the value of \(2^*\)?
(1) \(3^* = 2\) (2) \(5^* = 3\) Given =>x*=ax+a =>x*=a(x+1) Therefore =>2*=a(2+1) =>2*=3a  (1)so if we can find the value of 'a' we can hav the value of 2* Now Statement 1 says 3*=2 3*=4a from (1)=> 4a=2 => a=2/4=1/2 sufficient Statement 2 says 5*=3 5*=6a from (1)=> 6a=3 => a=3/6=1/2 sufficient Therefore option 'E' Thanks Hi Correct solution. But when each statement alone is sufficient to answer a question, the answer is D I guess that was a typo Hi Aman Thanks for the correction. Its 'D'




Re: For all x, the expression x* is defined to be ax + a, where a is......
[#permalink]
19 Dec 2017, 11:30






